Disease‐causing mutations in the XIAP BIR2 domain impair NOD2‐dependent immune signalling. Issue 8 (1st July 2013) - Damgaard, Rune Busk; Fiil, Berthe Katrine; Speckmann, Carsten; Yabal, Monica; Stadt, Udo zur; Bekker‐Jensen, Simon; Jost, Philipp J.; Ehl, Stephan; Mailand, Niels; Gyrd‐Hansen, Mads
<x xml:space="preserve">Abstract</x> X‐linked Inhibitor of Apoptosis (XIAP) is an essential ubiquitin ligase for pro‐inflammatory signalling downstream of the nucleotide‐binding oligomerization domain containing (NOD)‐1 and ‐2 pattern recognition receptors. Mutations in XIAP cause X‐linked lymphoproliferative syndrome type‐2 (XLP2), an immunodeficiency associated with a potentially fatal deregulation of the immune system, whose aetiology is not well understood. Here, we identify the XIAP baculovirus IAP repeat (BIR)2 domain as a hotspot for missense mutations in XLP2. We demonstrate that XLP2‐BIR2 mutations severely impair NOD1/2‐dependent immune signalling in primary cells from XLP2 patients and in reconstituted XIAP‐deficient cell lines. XLP2‐BIR2 mutations abolish the XIAP‐RIPK2 interaction resulting in impaired ubiquitylation of RIPK2 and recruitment of linear ubiquitin chain assembly complex (LUBAC) to the NOD2‐complex. We show that the RIPK2 binding site in XIAP overlaps with the BIR2 IBM‐binding pocket and find that a bivalent Smac mimetic compound (SMC) potently antagonises XIAP function downstream of NOD2 to limit signalling. These findings suggest that impaired immune signalling in response to NOD1/2 stimulation is a general defect in XLP2 and demonstrate that the XIAP BIR2‐RIPK2 interaction may be targeted pharmacologically to modulate inflammatory signalling.